Antecedents of zakat payers’trust in an emerging zakat sector : an exploratory study - Murtala Oladimeji , Abioye Mustafa; Mohamad, Muslim Har Sani; Adnan, Muhammad Akhyar (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to investigate and explain the factors underlying the inclination of zakat payers to trust a particular zakat institution. Design/methodology/approach – Based on the literature review and experience survey, a context specific questionnaire was developed as the main method of quantitative data collection. The instrument was administered to a sample of Muslim professionals who observe religious seclusion in the last ten days of the Islamic fasting month (itqaf) in 12 purposely selected mosques across four states and the federal capital territory. Findings – Drawn from the resource dependence and legitimacy theories, the study finds that board capital, disclosure practices, governmental model of zakat institution, and stakeholder management were identified through the use of structural equation modeling as being the antecedents of zakat payers’ trust. Originality/value – This paper is the first to report an empirically based model of zakat payers’ trust.